(untitled) (Bangladesh Journal of Nutrition, 2013)
Background: Nutritional status in relation to selected biochemical parameters and also nutrient intakes in the pre-eclampsia and eclampsia was assessed in 52 patients and compared with that of 52 normal pregnant (NP) women. Serum calcium, ascorbic acid and blood Hb levels in the pre-eclamptic and eclamptic patients were significantly lower than the values of NP women. By unpaired t-test demonstrated in our study, the serum calcium, ascorbic acid and blood Haemoglobin (Hb) level were highly significantly different but not correlated with each other when compared among these groups. However, total statistical analysis revealed that among all the factors studied serum calcium level, ascorbic acid level and blood Hb level have effect on nutritional status of pre-eclampsia and eclampsia. DOI: http://dx.doi.org/10.3329/bjnut.v24i0.14032 Bangladesh J. Nutr. Vol. 24-25 Dec 2011-2012 pp.7-14